PENCAPAIAN PRESTASI BELAJAR SAINS KELAS V SDN PADA MATERI SISTEM PERNAPASAN MELALUI METODE EKSPERIMEN - ningsih, yumila; fitria, yanti; yunisrul, yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to effect of experimental methods approach on student learnings outcomes in science  at 5th grade of elementary school in II Group Subdistrict payakumbuh of the academic year 2018/2019 with material for respiratory function. Type of this research is experiment used quasi experiment with Non-equivalent control group design. Sample of this research is students at 5th  grade elementary school 04 Taeh Baruah and students at 5th  grade elementary school 06 Taeh Baruah. Research sample is 15 students in elementary school 06 as experimental methods learning group and 15 students in elementary school 04 as conventional learning group that choosed based on purposive sampling technique. Result of research data calculation that used is t-test find thitung 1,8 > ttabel 1,7 on a 0,05 level. So, it can be concluded Ha accepted that there is influence the use of experimental methods on science learning outcomes at 5th grade of elementary school in II Group Subdistrict Payakumbuh.Keywords : Experiment Method, Learning Outcomes, Science